Inovasi Media Pembelajaran Matematika: Pemanfaatan Android dan Adobe Animate untuk Peningkatan Literasi Siswa pada Relasi dan Fungsi - -, Sutra; Majid, Ahmad Farham; Shadiq, Muh Ibnu; Kurniati (International Journal of Progressive Mathematics Education, 2025)
Purpose: This research aims to develop and evaluate the effectiveness of mathematics learning media utilizing Android and Adobe Animate on the topic of relations and functions, specifically to address the prevailing deficiency in students' mathematical literacy. Design/methodology/approach: The study employs a Research and Development (R&D) technique guided by the ADDIE model, encompassing the phases of analysis, design, development, implementation, and evaluation. The research subjects consisted of 21 tenth-grade students at MA Madani Pao-Pao, utilizing instruments such as expert validation sheets, teacher and student response questionnaires, and pretest-posttest assessments. Findings: The validation results for both media and content demonstrated "excellent" quality with a score of 87, while feasibility assessments from teachers and students reached 89%. Furthermore, the average student score rose from 60.5 (pretest) to 79.9 (posttest), yielding an N-gain value of 0.41 (moderate category); consequently, the developed media is proven to be valid, practical, and effective in enhancing conceptual understanding and mathematical literacy. Practical implications: The integration of technology into pedagogy fosters a more engaging and adaptive learning experience, thereby supporting the attainment of 21st-century competencies within literacy-based mathematics. Originality/value: This study contributes to the utilization of interactive Android and Adobe Animate-based media as a strategic solution to the primary challenges encountered in conventional teaching environments that lack interactive resources.   Purpose: Penelitian ini bertujuan untuk mengembangkan serta menguji efektivitas media pembelajaran matematika dengan pemanfaatan Android dan Adobe Animate pada materi relasi fungsi guna mengatasi rendahnya literasi matematika siswa. Design/methodology/approach: Teknik penelitian dan pengembangan (R&D) untuk studi ini memanfaatkan model ADDIE, yang terdiri dari fase analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian adalah 21 siswa kelas X MA Madani Pao-Pao dengan instrumen lembar validasi ahli, angket respons guru dan siswa, serta tes pretest-posttest. Findings: Hasil validasi media dan materi menunjukkan kualitas “sangat baik” dengan skor 87, dan hasil kelayakan dari guru dan siswa mencapai 89%. Nilai rata-rata siswa meningkat dari 60,5 (pretest) menjadi 79,9 (posttest), dengan nilai N-gain sebesar 0,41 (kategori sedang), sehingga media yang dikembangkan terbukti valid, praktis, dan efektif meningkatkan pemahaman konsep serta literasi matematika siswa. Practical implications: Integrasi teknologi ke dalam pembelajaran menciptakan pengalaman belajar yang lebih menarik, adaptif, dan mendukung pencapaian kompetensi abad ke-21 dalam matematika berbasis literasi. Originality/value: Penelitian ini memberikan kontribusi pada pemanfaatan media interaktif berbasis Android dan Adobe Animate sebagai solusi atas tantangan utama dalam pembelajaran konvensional dan minim media interaktif.